IDENTITY BUILDING OF ASIAN INDIANS IN AMERICAN SOCIETY - Yanti Haryanti (Jurnal Penelitian Humaniora, 2018)
ABSTRACTThis study discusses and explains the identity building of ethnic minority in American multicultural society. Identity is not given directly as the immigrants arrived in the States, but they had to get through hurdles and adjustment. Hence the comers need to have a negotiation strategy in getting into the mainstream. The analysis is done by using the interdisciplinary approaches to view on the historical, cultural, and sociological elements of the study. The writer develops the identity theory of Sheldon Stryker to reveal the process of identity building of the Asian Indian in American society. The result of this study shows that the Asian Indian immigrants bring their culture that made themselves attractive as well as accepted by the mainstream society. Besides, the Asian Indian immigrants are the people of hard work and clever that they can easily gain success in the United States and consequently support the country in the global competitiveness. The successes of the Asian Indian immigrants have created a positive identity in the American society. Fortunately, the maneuver of being multicultural in American society today has advantaged this minority group to continue their existence.